Timing of Stimulant Treatment for ADHD and Effect on Academic Progress - J Gordon Millichap (Pediatric Neurology Briefs, 2012)
Investigators at University of Iceland, Reykjavik, and other centers in Iceland and in USA studied the probability of academic decline (drop of >5.0 percentile points) in ADHD children according to drug exposure and timing of treatment start between National Scholastic Examinations.